Vascular access and its complications in patients with chronic kidney disease on haemodialysis: a retrospective analysis - Goplani, Kamal; Shrimali, Jigar; Prajapati, Amitkumar; Desai, Bhavin (International Journal of Research in Medical Sciences, 2020)
Background: Inadequate vascular access in patients on haemodialysis is a major cause of hospitalization leading to life threatening complications. This study evaluated the types of vascular access, location and associated complications in patients with chronic kidney disease (CKD) on haemodialysis. Methods: Patients with CKD stage V on haemodialysis were included in the study. The data was retrospectively collected including demographic details, comorbidities, serum creatinine, haemoglobin, type and site of access and associated complications. Results: A total of 82 patients with mean (SD) age of 56.6(13.9) years were included with 50 (60.9%) patients on arteriovenous fistula (AVF) access and remaining 32 (39.1%) on dual-lumen catheter (DLC). Hypertension (42.6%) was the most common comorbidity reported followed by diabetes (24.3%) and chronic glomerulonephritis (13.4%). In AVF access, 25 (50.0%) had wrist as site of access, 10 (20.0%) had forearm, 11(22.0%) had brachiocephalic and four (8.0%) brachiobasilic. Of 32 DLC access, 27(84.4%) had jugular vein and four (12.5%) femoral vein. One patient with AVF access reported venous hypertension; however, the complications reported in patients with DLC access were infection (n=6, 18.8%) and hematoma and venous hypertension (n=1, 3.7%, each). Conclusions: This study with limited sample size showed that the most common access site for AVF and DLC was wrist and jugular vein, respectively. Infection was the most common complication in patients with DLC. AVF is comparatively safe option for haemodialysis; however, DLC should be used only as a temporary option.